Human-Centered Design in Construction Software: Designing Interfaces for Non-Technical Field Personnel - Jasani, Darshit (International Journal of Computational and Experimental Science and Engineering, 2023)
This study investigates the integration of Human-Centered Design (HCD) principles in developing construction software interfaces for non-technical field personnel in the Indian construction sector. The research aims to optimize the usability of construction interfaces by considering local challenges such as high temperatures, glove use, and bilingual needs (Hindi-English). A usability experiment was conducted with 78 field personnel from 8 sites in Haryana and Maharashtra (2022–2023), using four prototypes tailored to specific environmental conditions. Key metrics included System Usability Scale (SUS), Task Load Index (TLX), error rates, and task completion times. The prototypes underwent iterative changes, focusing on reducing icon clutter, improving font size, enhancing button sizes, and incorporating voice feedback in Hindi and English. Results showed significant usability improvements across all metrics, with the final prototype (SAHF) achieving a 45.9-point improvement in SUS scores, a 60% reduction in errors, and a 72% improvement in task completion speed. This research underscores the importance of adapting technology to field-specific needs and highlights the positive impact of human-centered design on the efficiency and usability of construction software for non-technical users.